OPTIMAL CHOICE WITHIN A FAULT TOLERANT FLIGHT CONTROL SYSTEM - Kazak, Vasily; Shevchuk, Dmitriy; Bugryk, Sergiy; Smerechynskyy, Yuri (Proceedings of National Aviation University (archive), 2013)
Safety of aircraft during the flight is one of the most important problems that concerns of all aviation. Failures/faults main elements automatic control system and damages to the external contour of the aircraft by foreign objects always lead to a change the characteristics of the aircraft, direct and indirect economic costs and sometimes to injury or death of passengers and crew. Real-time active fault tolerant control system makes it possible to warn or prevent emergency situations and thus improve safety.